The Effect of Modernization of the Tax Administration System and Tax Sanctions on Taxpayer Compliance: The Effect of Modernization of the Tax Administration System and Tax Sanctions on Taxpayer Compliance - Era, Annathasia Puji Erasashanti; Irsan Lubis, Yuni Andriani, Ridarmelli, (ADPEBI, 2022)
This study aims to determine the effect of modern tax administration system and tax sanction on tax compliance. The dependent variable in this study is taxpayer compliance, while the independent variable in this study is the modernization of the tax administration system and tax sanctions. This study uses a quantitative approach. The population in this study are corporate taxpayers who are registered at Bogor Tax Service Office. The sampling technique was carried out using the convenience sampling method. Data collection techniques were carried out using questionnaires and data analysis techniques using multiple linear regression analysis with SPSS software. The results of the study are the modernization of the tax administration system and tax sanctions have a positive effect on taxpayer compliance.